SABA: A Testbed for a Real-Time MIMO System - Brühl Lars; Keusgen Wilhem; Borkowski Daniel; Degen Christoph; Alirezaei Gholamreza; Geschewski Frank; Oikonomopoulos Christos; Rembold Bernhard (EURASIP Journal on Advances in Signal Processing, 2006)
The growing demand for high data rates for wireless communication systems leads to the development of new technologies to increase the channel capacity thus increasing the data rate. MIMO (multiple-input multiple-output) systems are best qualified for these applications. In this paper, we present a MIMO test environment for high data rate transmissions in frequency-selective environments. An overview of the testbed is given, including the analyzed algorithms, the digital signal processing with a new highly parallel processor to perform the algorithms in real time, as well as the analog front-ends. A brief overview of the influence of polarization on the channel capacity is given as well.